ANALISIS PERAN QUANTITY SURVEYOR PADA PROYEK JISC (JATILUHUR INDUSTRIAL SMART CITY) - Theddy, Vincent; Asriningsih Pranoto, Wati (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2024)
Infrastructure development in Indonesia continues to increase overtime, not only in the capital area but in other cities as well. With infrastructure development in Indonesia, the need for labor has also increased. Not only are contractors, architects or consultants needed, but there are also quantity surveyors. QS’s a job that has an important role in construction. However, QS are still not well known by students or the general public. One of the roles of QS is to calculate cost estimates for construction, but there are still many roles for a QS. The problem to be discussed in this research is the role of quantity surveyors in the Jatiluhur Industrial Smart City (JISC) project, especially on the owner's side. The purpose of this discussion is to find out what QS’s role is, especially on the owner's side. The research method is to conduct a literature study. Literature studies are carried out by reading and studying several journals and books. The results of the literature study were analyzed and concluded. QS is a job that is really needed by the owner to run the project smoothly. QS's role includes making BQs, participating in tenders, making work orders, controlling construction progress, procuring goods. Abstrak Pembangunan infrastruktur di Indonesia seiring waktu terus bertambah, tidak hanya di daerah ibukota saja melainkan di kota-kota lainnya juga. Dengan adanya Pembangunan infrastruktur di Indonesia ini kebutuhan akan tenaga kerja pun meningkat. Tidak hanya kontraktor, arsitek, ataupun konsultan yang dibutuhkan dalam suatu proyek, melainkan ada juga quantity surveyor. Quantity surveyor merupakan salah satu pekerjaan yang memiliki peran penting dalam sebuah konstruksi. Namun quantity surveyor masih belum terlalu dikenal oleh mahasiswa atau masyarakat umum. Salah satu peran quantity surveyor adalah menghitung estimasi/perkiraan biaya pada suatu konstruksi. Quantity surveyor melakukan estimasi biaya dengan membuat rancangan anggaran biaya atau bill of quantities. Bill of quantities dibuat berdasarkan gambar dan spesifikasi proyek. Permasalahan yang ingin dibahas pada jurnal ini adalah peran quantity surveyor pada proyek JISC terutama pada pihak owner pada proyek JISC. Tujuan dari pembahasan ini adalah untuk mengetahui apa saja peran quantity surveyor terutama pada pihak owner pada proyek JISC dari tahap awal hingga akhir. Metode penelitian yang digunakan pada penelitian ini ada pengumpulan data primer dan sekunder. Dengan penelitian primer berupa studi literatur atau studi kepustakaan dengan membaca dan mempelajari jurnal dan buku dan sekunder berupa observasi dan wawancara dengan quantity surveyor.